CD161++CD8+ T cells, including the MAIT cell subset, are specifically activated by IL‐12+IL‐18 in a TCR‐independent manner. Issue 1 (1st October 2013) - Ussher, James E.; Bilton, Matthew; Attwod, Emma; Shadwell, Jonathan; Richardson, Rachel; de, Catherine; Mettke, Elisabeth; Kurioka, Ayako; Hansen, Ted H.; Klenerman, Paul; Willberg, Christian B.
<x xml:space="preserve">Abstract</x> CD161++CD8+ T cells represent a novel subset that is dominated in adult peripheral blood by mucosal‐associated invariant T (MAIT) cells, as defined by the expression of a variable‐α chain 7.2 (Vα7.2)‐Jα33 TCR, and IL‐18Rα. Stimulation with IL‐18+IL‐12 is known to induce IFN‐γ by both NK cells and, to a more limited extent, T cells. Here, we show the CD161++ CD8+ T‐cell population is the primary T‐cell population triggered by this mechanism. Both CD161++Vα7.2+ and CD161++Vα7.2− T‐cell subsets responded to IL‐12+IL‐18 stimulation, demonstrating this response was not restricted to the MAIT cells, but to the CD161++ phenotype. Bacteria and TLR agonists also indirectly triggered IFN‐γ expression via IL‐12 and IL‐18. These data show that CD161++ T cells are the predominant T‐cell population that responds directly to IL‐12+IL‐18 stimulation. Furthermore, our findings broaden the potential role of MAIT cells beyond bacterial responsiveness to potentially include viral infections and other inflammatory stimuli.